Preparation method of modified aluminum lithium alloy powder and powder

By forming LiF and AlF3 attachments and cellulose acetate wax-based cladding on the surface of aluminum-lithium alloy powder, the combustion stability and heat release of modified aluminum-lithium alloy powder are solved, and the combustion efficiency and heat release are significantly improved.

CN119259995APending Publication Date: 2025-01-07BGRIMM ADVANCED MATERIALS SCI & TECH CO LTD +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411503564.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-25
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

The existing modified aluminum-lithium alloy powders have limited stability during combustion, and the combustion efficiency and actual heat released are insufficient. This is mainly due to the addition of lithium, which causes the metal to be oxidized, which reduces the active metal content and combustion performance.

Method used

By dispersing the aluminum-lithium alloy powder in an organic solvent, adding dry inert gas and hydrofluoric acid, surface attachments of LiF and AlF3 are formed, and cellulose acetate and wax substances are used as coating agents to coat aluminum-lithium alloys. The powder surface was vacuum dried to form a modified aluminum lithium alloy powder.

Benefits of technology

It significantly improves the stability and combustion efficiency of aluminum-lithium alloy powder, reduces the proportion of uncombustible powder, significantly improves the actual heat released, and enhances the energy density and combustion performance of the fuel.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119259995A_ABST
    Figure CN119259995A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of metal powder material preparation, and particularly relates to a preparation method of modified aluminum lithium alloy powder and the powder. The preparation method comprises the following steps: dispersing aluminum-lithium alloy powder in an organic solvent to obtain a first alloy powder dispersion liquid; introducing dry inert gas into the first alloy powder dispersion liquid, adding hydrofluoric acid, and reacting to obtain second alloy powder dispersion liquid; a coating agent is dissolved in an organic solvent, a coating agent solution is obtained, and the coating agent comprises cellulose acetate and a wax substance; and adding a coating agent solution into the second alloy powder dispersion liquid, stirring at a preset temperature to volatilize the organic solvent and coat the alloy powder with the coating agent, and then carrying out vacuum drying to obtain the modified aluminum-lithium alloy powder. The modified aluminum-lithium alloy powder is good in stability, high in combustion efficiency and capable of actually releasing much heat.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of metal powder material preparation, and in particular, relates to a preparation method of modified aluminum-lithium alloy powder and the powder. Background Art

[0002] Aluminum-lithium alloy powder has good thermal reaction activity. Its application as a high-energy additive in fields such as solid propellants has been a key research direction in recent years. However, due to the addition of lithium, a network structure is formed on the surface of the alloy, and oxygen can easily enter the interior of the powder, causing the metal to be continuously oxidized, reducing the active metal content of the aluminum-lithium alloy powder, and ultimately reducing its stability and combustion performance.

[0003] It has been proposed to set a coating layer on the surface of aluminum-lithium alloy powder to improve the stability of aluminum-lithium alloy powder. Organic acids, aluminum stearate, polysiloxane, polyethylene glycol, etc. have been used as coating layers for aluminum-lithium alloy powder. However, it is found that the stability of aluminum-lithium alloy powder is still limited. When the powder is used as an energetic additive, the combustion efficiency is limited and the actual heat released is limited.

[0004] It should be noted that this part of the present invention only provides background technology related to the present invention and does not necessarily constitute prior art or known technology. Summary of the invention

[0005] The purpose of the present invention is to overcome the defects of the existing modified aluminum-lithium alloy powder with a coating layer, such as limited stability, efficiency during combustion and limited heat actually released, and to provide a method for preparing a modified aluminum-lithium alloy powder and a powder, wherein the modified powder has high stability, high efficiency during combustion and actually releases a lot of heat.

[0006] In order to achieve the above object, in a first aspect, the present invention provides a method for preparing a modified aluminum-lithium alloy powder, comprising: dispersing aluminum-lithium alloy powder in an organic solvent to obtain a first alloy powder dispersion; Passing dry inert gas into the first alloy powder dispersion, and then adding hydrofluoric acid to obtain a second alloy powder dispersion after reaction; dissolving a coating agent in the organic solvent to obtain a coating agent solution, wherein the coating agent includes cellulose acetate and a wax substance; The coating agent solution is added to the second alloy powder dispersion, and stirred at a preset temperature to allow the organic solvent to volatilize and the coating agent to coat the alloy powder, followed by vacuum drying to obtain modified aluminum-lithium alloy powder.

[0007] In some preferred embodiments, the average particle size of the aluminum-lithium alloy powder is 1 μm to 100 μm.

[0008] Preferably, when the concentration of hydrofluoric acid is 1wt%-5wt%, 0.1ml-0.5ml of hydrofluoric acid is added per gram of the aluminum-lithium alloy powder.

[0009] Preferably, the ratio of the mass of the coating agent to the mass of the aluminum-lithium alloy powder is 0.05-0.2.

[0010] In some preferred embodiments, after adding hydrofluoric acid, the mixture is reacted at a temperature of 30° C. to 50° C. to obtain the second alloy powder dispersion.

[0011] In some preferred embodiments, the wax substance is paraffin.

[0012] Preferably, the ratio of the mass of cellulose acetate to the mass of paraffin in the coating agent is 0.2-0.8.

[0013] Preferably, the preset temperature is 50°C~100°C.

[0014] In some preferred embodiments, the organic solvent is selected from at least one of acetone, ethanol, n-heptane, ethyl acetate, and acetonitrile; And / or, the vacuum drying conditions include: the vacuum degree is not greater than 0.095 MPa, and the drying temperature is 50° C. to 80° C.

[0015] In a second aspect, the present invention provides a modified aluminum-lithium alloy powder, which is prepared by the preparation method described in the first aspect, wherein the modified aluminum-lithium alloy powder comprises an aluminum-lithium alloy core and a coating layer coated on the outside of the aluminum-lithium alloy core, and the coating layer comprises cellulose acetate and a wax substance.

[0016] The preparation method of the modified aluminum-lithium alloy powder of the present invention comprises preparing the aluminum-lithium alloy powder into a dispersion, adding cellulose acetate and a wax substance as a coating agent solution of a coating agent, stirring at a preset temperature to volatilize the organic solvent and coat the alloy powder with the coating agent, and then vacuum drying to obtain the modified aluminum-lithium alloy powder. The modified aluminum-lithium alloy powder comprises an aluminum-lithium alloy core and a coating layer containing cellulose acetate and a wax substance, which can inhibit the reaction of the aluminum-lithium alloy powder with air and water, improve the stability of the aluminum-lithium alloy powder and the effective metal content, and burn more evenly and fully when used, significantly reduce the proportion of unburned powder, and significantly improve the powder combustion efficiency and the actual heat released. Before adding the coating agent solution, dry gas is introduced into the first alloy powder dispersion and then hydrofluoric acid is added, which can remove the aluminum and lithium oxides remaining on the surface of the aluminum-lithium alloy powder before coating, and can improve the powder combustion efficiency and the actual heat released. After the addition of hydrofluoric acid, LiF and AlF3 will be attached to the surface of the aluminum-lithium alloy core. LiF can increase the energy density of the fuel and the actual heat released during combustion. AlF3 will sublimate when the aluminum-lithium alloy powder is burned, which can promote the dissociation of agglomerated aluminum particles, improve the powder combustion efficiency and the actual heat released. The introduction of dry gas can take away a small amount of water formed after the addition of hydrofluoric acid, prevent the lithium element in the aluminum-lithium alloy powder from reacting with water, and improve the powder combustion efficiency and heat release. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.

[0018] Figure 1 This is a transmission electron microscope photograph of the modified aluminum-lithium alloy powder of Example 1 of the present invention.

[0019] Figure 2 This is the EDS analysis spectrum of the coating layer of the modified aluminum-lithium alloy powder of Example 1 of the present invention.

[0020] Figure 3 1 is a comparative XRD spectrum of the initial aluminum-lithium alloy powder before coating and the modified aluminum-lithium alloy powder after coating in Example 1 of the present invention. DETAILED DESCRIPTION

[0021] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0022] The inventors of the present application have found through research that the existing modified aluminum-lithium alloy powder with a coating layer has limited stability, and its efficiency and actual heat release during combustion are limited.

[0023] In this regard, in a first aspect, the present invention provides a method for preparing a modified aluminum-lithium alloy powder, comprising: dispersing aluminum-lithium alloy powder in an organic solvent to obtain a first alloy powder dispersion; Passing dry inert gas into the first alloy powder dispersion, and then adding hydrofluoric acid to obtain a second alloy powder dispersion after reaction; dissolving a coating agent in the organic solvent to obtain a coating agent solution, wherein the coating agent includes cellulose acetate and a wax substance; The coating agent solution is added to the second alloy powder dispersion, and stirred at a preset temperature to allow the organic solvent to volatilize and the coating agent to coat the alloy powder, followed by vacuum drying to obtain modified aluminum-lithium alloy powder.

[0024] The preparation method of the modified aluminum-lithium alloy powder of the present invention comprises the following steps: dispersing the aluminum-lithium alloy powder in an organic solvent to obtain a first alloy powder dispersion, introducing a dry gas into the first alloy powder dispersion and then adding hydrofluoric acid to react to obtain a second alloy powder dispersion, adding a coating agent solution including cellulose acetate and a wax substance to the second alloy powder dispersion, stirring at a preset temperature, and then vacuum drying to obtain a modified aluminum-lithium alloy powder including an aluminum-lithium alloy core and a coating layer coated on the surface of the core, wherein the coating layer has cellulose acetate and a wax substance. The coating layer contains wax substances, which can prevent aluminum, lithium elements from reacting with oxygen or water to generate impurities such as aluminum oxide and lithium hydroxide, thereby improving the stability of the aluminum-lithium alloy powder, increasing the active metal content of the lithium-aluminum alloy powder, and improving the powder combustion efficiency and the heat released during combustion. The coating layer contains cellulose acetate, which is coated on the surface, volatilizes during combustion, and is distributed in the aluminum-lithium alloy fuel in the form of gas, which can reduce the combustion rate of the aluminum-lithium alloy powder. The aluminum-lithium alloy powder burns more evenly and fully during use, significantly reducing the proportion of unburned powder, and significantly improving the powder combustion efficiency and the actual heat released during combustion.

[0025] Before adding the coating agent solution, adding hydrofluoric acid to the alloy powder dispersion can remove the aluminum and lithium oxides remaining on the surface of the aluminum-lithium alloy powder before coating, which can improve the powder combustion efficiency and the actual heat released. After adding hydrofluoric acid, the surface of the aluminum-lithium alloy core obtained will be attached with LiF and / or AlF3. When the aluminum-lithium alloy powder is burned, LiF reacts with the hydrogen in the fuel to release a large amount of heat energy, which can increase the combustion temperature of the fuel, increase the energy density of the fuel and the actual heat released during combustion. AlF3 will sublimate when the aluminum-lithium alloy powder is burned, which can reduce the generation of solid phase products, promote the dissociation of agglomerated aluminum particles, and the dissociated aluminum particles are easier to burn, which can reduce the proportion of unburned aluminum-lithium particles, improve the powder combustion efficiency and the actual heat released. Before adding hydrofluoric acid to the first alloy powder dispersion, a dry inert gas is introduced into the dispersion to take away a small amount of water formed after the addition of hydrofluoric acid, prevent the lithium element in the aluminum-lithium alloy powder from reacting with water, avoid side reactions, and improve the powder combustion efficiency and the heat released during combustion.

[0026] The wax material of the present invention can prevent aluminum and lithium elements from reacting with oxygen or water, and maintain the form of single aluminum and lithium. Cellulose acetate evaporates during combustion, and is distributed in the aluminum-lithium alloy fuel in a gaseous form. AlF3 sublimates during combustion, and can promote the dissociation of agglomerated aluminum particles. The aluminum-lithium alloy particles separated by gas and the dissociated aluminum particles are more likely to burn. LiF reacts with hydrogen in the fuel during combustion of the aluminum-lithium alloy powder, and releases a large amount of heat energy. The aluminum-lithium alloy fuel can be fully burned through the synergistic effect of the aluminum-lithium alloy core, the AlF3 and LiF on the surface of the aluminum-lithium alloy core, the wax material, and the cellulose acetate coating layer, and the powder combustion efficiency and the heat actually released during combustion are significantly improved.

[0027] The present invention does not limit the type of dry inert gas, and specifically, for example, it can be dry argon or dry nitrogen. The present invention does not limit the dispersion method for dispersing the aluminum-lithium alloy powder in the organic solvent, and specifically, for example, it can be ultrasonic dispersion or stirring, or stirring while ultrasonic dispersion. It can be understood that the lithium-aluminum alloy powder is dispersed in the organic solvent under an inert atmosphere, and the coating agent solution is added to the second alloy powder dispersion under an inert atmosphere. Preferably, hydrofluoric acid is added dropwise to the first alloy powder dispersion while stirring. The present invention can add the coating agent solution while stirring, or stir after adding the coating agent solution.

[0028] In some preferred embodiments, the average particle size of the aluminum-lithium alloy powder is 1 μm to 100 μm. Under this preferred embodiment, it is more conducive to improving the powder combustion efficiency and the actual heat released during combustion. The average particle size of the aluminum-lithium alloy powder can be, for example, 1 μm, 15 μm, 30 μm, 45 μm, 60 μm, 75 μm, 90 μm and 100 μm.

[0029] Preferably, when the concentration of hydrofluoric acid is 1wt%-5wt%, 0.1ml~0.5ml of hydrofluoric acid is added relative to each gram of the aluminum-lithium alloy powder. On the basis that the average particle size of the aluminum-lithium alloy powder is 1μm~100μm, under this preferred embodiment, the amount of hydrofluoric acid added is not less than 0.1ml, which is more conducive to fully removing the aluminum and lithium oxides remaining on the surface of the aluminum-lithium alloy powder before coating, fully converting the aluminum oxide into AlF3, improving the powder combustion efficiency and the actual heat released, and fully converting the lithium oxide into LiF, improving the energy density of the fuel and the actual heat released during combustion, not more than 0.5ml, which is more conducive to avoiding the reaction of hydrofluoric acid with aluminum and lithium inside the aluminum-lithium alloy powder, resulting in a decrease in the effective content of aluminum and lithium, thereby improving the powder combustion efficiency and the actual heat released. The amount of hydrofluoric acid can be, for example, 0.1ml, 0.2ml, 0.3ml, 0.4ml and 0.5ml.

[0030] Preferably, the ratio of the mass of the coating agent to the mass of the aluminum-lithium alloy powder is 0.05 to 0.2. On the basis that the average particle size of the aluminum-lithium alloy powder is 1 μm to 100 μm, under this preferred scheme, the ratio of the mass of the coating agent to the mass of the aluminum-lithium alloy powder is 0.05 to 0.2, which is more conducive to effectively coating the lithium-aluminum alloy powder, fully forming the modified aluminum-lithium alloy powder, avoiding the reaction of aluminum, lithium elements and oxygen or water to generate impurities such as aluminum oxide and lithium hydroxide, improving the stability of the aluminum-lithium alloy powder, increasing the active metal content of the lithium-aluminum alloy powder, increasing the powder combustion efficiency and the actual heat released, giving full play to the role of cellulose acetate, making the aluminum-lithium alloy powder burn more evenly and fully when used, further improving the powder combustion efficiency and the actual heat released, avoiding the coating layer being too thick, increasing the proportion of the effective components aluminum and lithium, and increasing the calorific value of the product.

[0031] In some preferred embodiments, after adding hydrofluoric acid, the reaction is carried out at a temperature of 30°C to 50°C to obtain a second alloy powder dispersion. The inventors found that the reaction temperature of hydrofluoric acid is 30°C to 50°C, which is more conducive to fully removing the aluminum and lithium oxides remaining on the surface of the aluminum-lithium alloy powder before coating, improving the powder combustion efficiency and the actual heat released, and fully converting the aluminum and lithium oxides into LiF and AlF 3, Improve the energy density of the fuel, the actual heat released during combustion, and the powder combustion efficiency. The reaction temperature after adding hydrofluoric acid can be, for example, 30°C, 35°C, 40°C, 45°C, and 50°C. After adding hydrofluoric acid to the first alloy powder dispersion, the present invention keeps the temperature at a temperature of 30°C to 50°C for a preset time. The inventors found that a holding time of 1h to 3h is more conducive to fully removing the residual aluminum and lithium oxides on the surface of the aluminum-lithium alloy powder before coating, and fully converting the aluminum and lithium oxides into LiF and AlF3.

[0032] In some preferred embodiments, the wax material is paraffin. The inventors have found that the wax material is paraffin, which is more conducive to avoiding the reaction of aluminum, lithium elements and oxygen or water to generate impurities such as aluminum oxide and lithium hydroxide, improving the stability of aluminum-lithium alloy powder, increasing the active metal content of lithium-aluminum alloy powder, and improving the powder combustion efficiency and the actual heat released.

[0033] Preferably, the ratio of the mass of cellulose acetate to the mass of paraffin in the coating agent is 0.2 to 0.8. The inventors found that the ratio of the mass of cellulose acetate to the mass of paraffin in the coating agent is not less than 0.2, which is more conducive to the uniform and full combustion of the aluminum-lithium alloy powder during use, reduces the proportion of unburned powder, and improves the powder combustion efficiency and the actual heat released. The ratio of the mass of cellulose acetate to the mass of paraffin is not higher than 0.8, which is more conducive to avoiding the reaction of aluminum, lithium elements and oxygen or water to generate impurities such as aluminum oxide and lithium hydroxide, improves the stability of the aluminum-lithium alloy powder, increases the active metal content of the lithium-aluminum alloy powder, and improves the powder combustion efficiency and the actual heat released. The ratio of the mass of cellulose acetate to the mass of paraffin can be, for example, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7 and 0.8.

[0034] Preferably, the preset temperature is 50°C to 100°C. The inventors found that after adding the coating agent solution including cellulose acetate and wax substances, stirring at a temperature of 50°C to 100°C is more conducive to forming a coating layer with uniform thickness and composition on the surface of the aluminum-lithium alloy core, avoiding the volatilization of cellulose acetate and wax substances and failing to fully coat, thereby improving the powder combustion efficiency and the actual heat released. The preset temperature can be, for example, 50°C, 60°C, 70°C, 80°C, 90°C and 100°C.

[0035] The present invention does not limit the type of organic solvent. In some preferred embodiments, the organic solvent is selected from at least one of acetone, ethanol, n-heptane, ethyl acetate, and acetonitrile, which is more conducive to the full dissolution of the coating agent and the formation of a coating layer with uniform thickness and composition on the surface of the aluminum-lithium alloy core.

[0036] In some preferred embodiments, the vacuum drying conditions include: the vacuum degree is not greater than 0.095MPa, and the drying temperature is 50°C to 80°C. The inventors found that the drying temperature is 50°C to 80°C, which is more conducive to improving the drying efficiency while inhibiting oxidation and ensuring the structure of the modified aluminum-lithium alloy powder (aluminum-lithium alloy core and a coating layer coated outside the core). After vacuum drying of the present invention, crushing and screening are preferably performed to obtain modified aluminum-lithium alloy powder. The drying temperature can be, for example, 50°C, 60°C, 70°C and 80°C.

[0037] In a second aspect, the present invention provides a modified aluminum-lithium alloy powder, which is prepared by the preparation method described in the first aspect, and the modified aluminum-lithium alloy powder includes an aluminum-lithium alloy core with lithium fluoride and / or aluminum fluoride attached to the surface and a coating layer coated on the outside of the aluminum-lithium alloy core, and the coating layer includes cellulose acetate and a wax substance.

[0038] Under this preferred embodiment, the coating layer has cellulose acetate, and the aluminum-lithium alloy powder burns more evenly and fully during use, significantly reducing the proportion of unburned powder. The coating layer has wax substances, which improve the stability of the aluminum-lithium alloy powder and increase the active metal content of the lithium-aluminum alloy powder, thereby significantly improving the powder combustion efficiency and the actual amount of heat released. Lithium fluoride is attached to the surface of the inner core, which can increase the combustion temperature of the fuel, increase the energy density of the fuel and the actual amount of heat released during combustion. Aluminum fluoride is attached to the surface of the inner core, which sublimates when the aluminum-lithium alloy powder burns, promotes the dissociation of agglomerated aluminum particles, and improves the powder combustion efficiency and the actual amount of heat released.

[0039] The modified aluminum-lithium alloy powder of the present invention has an aluminum-lithium alloy in the innermost layer, an aluminum fluoride and / or lithium fluoride in the middle layer, and an outermost layer which is a coating layer containing cellulose acetate and wax substances.

[0040] The present invention is further described in detail below with reference to specific embodiments.

[0041] Example 1 A method for preparing modified aluminum-lithium alloy powder, comprising the following steps: Step 1: Add 1 g of aluminum-lithium alloy powder to ethanol, the average particle size of the aluminum-lithium alloy powder is 50 μm, and stir under nitrogen atmosphere while ultrasonically dispersing to obtain a first alloy powder dispersion, the aluminum content of the aluminum-lithium alloy powder is 92.3 wt%, and the lithium content is 5.12 wt%; Step 2: Dry nitrogen was introduced into the first alloy powder dispersion, and hydrofluoric acid with a concentration of 3 wt% was added dropwise to the first alloy powder dispersion while stirring, and the amount of hydrofluoric acid added was 0.3 ml. After the hydrofluoric acid was added dropwise, the mixture was kept at 45° C. for 2 h to obtain a second alloy powder dispersion; Step 3: dissolve the coating agent in ethanol to obtain a coating agent solution, wherein the coating agent is cellulose acetate and paraffin, the ratio of the sum of the masses of paraffin and cellulose acetate to the mass of the aluminum-lithium alloy powder is 0.1, and the ratio of the mass of cellulose acetate to the mass of paraffin is 0.5. While stirring, add the coating agent solution to the second alloy powder dispersion, raise the temperature to 60°C, stir for 2 hours, so that the paraffin and cellulose acetate are coated on the surface of the aluminum-lithium alloy powder and the ethanol is volatilized, vacuum dry, crush and screen to obtain modified aluminum-lithium alloy powder, the vacuum degree of vacuum drying is not greater than 0.095MPa, and the drying temperature is 60°C.

[0042] The modified aluminum-lithium alloy powder was characterized by transmission electron microscopy. The morphology of the modified aluminum-lithium alloy powder can be found in Figure 1 ,right Figure 1 The coating layer on the surface was subjected to EDS analysis. The analysis results are shown in Figure 2 The coating layer contains C and O elements, and the modified aluminum-lithium alloy powder is coated with paraffin and cellulose acetate outside the aluminum-lithium alloy. Figure 3 The XRD diagrams of the initial aluminum-lithium alloy powder of step one before coating and the prepared modified aluminum-lithium alloy powder after coating show that there is no obvious change in the physical phase before and after coating, indicating that the modification process of the aluminum-lithium alloy powder has no effect on the metal crystal form. The newly prepared modified aluminum-lithium alloy powder was subjected to TG-DTA test, and the weight gain of the active component by oxidation was 69.8wt%. After being placed in the air for 7 days, the TG-DTA test was performed again, and the weight gain of the active component by oxidation was 67.5wt%. The weight gain of the active component by oxidation changed very little. After being placed in the air for 7 days, the active metal content of the modified aluminum-lithium alloy powder changed very little, and the modified aluminum-lithium alloy powder had excellent stability.

[0043] Example 2 The preparation method of Example 1 was used, except that in step 2, the amount of hydrofluoric acid added was 0.6 ml. The modified aluminum-lithium alloy powder was characterized by the same method as in Example 1. A coating layer was formed on the surface of the aluminum-lithium alloy powder. The modification process of the aluminum-lithium alloy powder did not affect the metal crystal form. The newly prepared modified aluminum-lithium alloy powder was subjected to TG-DTA test, and the oxidation weight gain of the active component was 69.4%.

[0044] Example 3 The preparation method of Example 1 is referred to, except that the ratio of the amount of coating agent added in step 3 to the mass of the aluminum-lithium alloy powder is 0.04. The modified aluminum-lithium alloy powder is characterized by the same method as in Example 1. Paraffin and cellulose acetate coating layers are formed on the surface of the aluminum-lithium alloy powder. The modification process of the aluminum-lithium alloy powder does not affect the metal crystal form. The newly prepared modified aluminum-lithium alloy powder is subjected to TG-DTA test, and the oxidation weight gain of the active component is 69.9wt%. After being placed in the air for 7 days, the TG-DTA test is performed again. The oxidation weight gain of the active component of the aluminum-lithium alloy powder is 66.1%. The oxidation weight gain of the active component changes little, and the modified aluminum-lithium alloy powder has good stability.

[0045] Example 4 The preparation method of Example 1 was used as reference, except that in step 2, after adding hydrofluoric acid, the mixture was kept at 20°C for 2 hours to obtain a second alloy powder dispersion. The modified aluminum-lithium alloy powder was characterized by the same method as in Example 1. A coating layer of paraffin and cellulose acetate was formed on the surface of the aluminum-lithium alloy powder, and the modification process of the aluminum-lithium alloy powder did not affect the metal crystal form.

[0046] Example 5 The preparation method of Example 1 was used, except that the ratio of the mass of cellulose acetate to the mass of paraffin was 0.1. The modified aluminum-lithium alloy powder was characterized by the same method as in Example 1. A coating layer of paraffin and cellulose acetate was formed on the surface of the aluminum-lithium alloy powder, and the modification process of the aluminum-lithium alloy powder did not affect the metal crystal form.

[0047] Example 6 The preparation method of Example 1 was used, except that the ratio of the mass of cellulose acetate to the mass of the wax substance was 0.9. The modified aluminum-lithium alloy powder was characterized by the same method as in Example 1. A coating layer of paraffin and cellulose acetate was formed on the surface of the aluminum-lithium alloy powder. The modification process of the aluminum-lithium alloy powder did not affect the metal crystal form. The newly prepared modified aluminum-lithium alloy powder was subjected to TG-DTA test. The oxidation weight gain of the active component was 69.7wt%. After being placed in the air for 7 days, the TG-DTA test was performed again. The oxidation weight gain of the active component of the aluminum-lithium alloy powder was 63.5%. The oxidation weight gain of the active component changed little, and the modified aluminum-lithium alloy powder had good stability.

[0048] Example 7 The preparation method of Example 1 is referred to, except that in step 3, after adding the coating agent solution to the second alloy powder dispersion, the temperature is raised to 110°C and stirred for 2 hours. The modified aluminum-lithium alloy powder is characterized by the same method as in Example 1. A coating layer of paraffin and cellulose acetate is formed on the surface of the aluminum-lithium alloy powder. The modification process of the aluminum-lithium alloy powder does not affect the metal crystal form. The newly prepared modified aluminum-lithium alloy powder is subjected to TG-DTA test, and the oxidation weight gain of the active component is 69.8wt%. After being placed in the air for 7 days, the TG-DTA test is performed again. The oxidation weight gain of the active component of the aluminum-lithium alloy powder is 62.6%, and the oxidation weight gain of the active component changes little. The modified aluminum-lithium alloy powder has good stability.

[0049] Comparative Example 1 The preparation method of Example 1 was used as reference, except that the coating agent did not include cellulose acetate, only paraffin was added, and the amount of the coating agent added remained unchanged. The modified aluminum-lithium alloy powder was characterized by the same method as in Example 1, and a paraffin coating layer was formed on the surface of the aluminum-lithium alloy powder, and the modification process of the aluminum-lithium alloy powder did not affect the metal crystal form.

[0050] Comparative Example 2 The preparation method of Example 1 was used, except that in step 2, the step of adding hydrofluoric acid was not performed. The modified aluminum-lithium alloy powder was characterized by the same method as in Example 1. A coating layer of paraffin and cellulose acetate was formed on the surface of the aluminum-lithium alloy powder, and the modification process of the aluminum-lithium alloy powder did not affect the metal crystal form.

[0051] Comparative Example 3 The preparation method of Example 1 was used as reference, except that in step 2, dry nitrogen was not introduced into the first alloy powder dispersion before the hydrofluoric acid was added. The modified aluminum-lithium alloy powder was characterized by the same method as in Example 1. A coating layer of paraffin and cellulose acetate was formed on the surface of the aluminum-lithium alloy powder, and the modification process of the aluminum-lithium alloy powder did not affect the metal crystal form.

[0052] Test Case Modified aluminum-lithium alloy powders were prepared according to the preparation methods of Examples 1 to 7 and Comparative Examples 1 to 3, and the combustion calorific value of the newly prepared modified aluminum-lithium alloy powders was tested using an oxygen bomb calorimeter. The newly prepared modified aluminum-lithium alloy powders were placed in the air for 7 days and then tested again. The results are shown in Table 1.

[0053]

[0054] Comparing Example 1 with Example 2, the amount of hydrofluoric acid added is not more than 0.5 ml, which is more conducive to increasing the effective content of aluminum and lithium, improving the powder combustion efficiency and the actual heat released. Comparing Example 1 with Example 3, the ratio of the mass of the coating agent to the mass of the aluminum-lithium alloy powder is not less than 0.05, which is more conducive to improving the stability of the alloy powder, improving the powder combustion efficiency and the actual heat released. Comparing Example 1 with Example 4, after adding hydrofluoric acid, the reaction is carried out at a temperature of 30°C to 50°C, which is more conducive to improving the powder combustion efficiency and the actual heat released. Comparing Example 1 with Example 4, after adding hydrofluoric acid, the reaction is carried out at a temperature of 30°C to 50°C, which is more conducive to improving the powder combustion efficiency and the actual heat released. Compared with Example 5, the ratio of the mass of cellulose acetate in the coating agent to the mass of paraffin is not less than 0.2, which is more conducive to improving the powder combustion efficiency and the actual heat released. Compared with Example 1 and Example 6, the ratio of the mass of cellulose acetate in the coating agent to the mass of paraffin is not higher than 0.8, which is more conducive to improving the stability of the alloy powder. Compared with Example 1 and Example 7, after adding the coating agent solution to the second alloy powder dispersion, coating at a temperature of 50°C to 100°C is more conducive to improving the stability of the alloy powder, improving the powder combustion efficiency and the actual heat released.

[0055] Comparing Example 1 with Comparative Example 1, cellulose acetate and paraffin are used for co-coating. Compared with coating with paraffin only, the powder combustion efficiency and the actual heat released during combustion can be improved. Comparing Example 1 with Comparative Example 2, the aluminum-lithium alloy powder is treated with hydrofluoric acid before coating, which can improve the powder combustion efficiency and the actual heat released. Comparing Example 1 with Comparative Example 3, dry inert gas is introduced into the alloy powder dispersion before adding hydrofluoric acid treatment, which can improve the powder combustion efficiency and the heat released during combustion.

[0056] Compared with the uncoated initial aluminum-lithium alloy powder, the scheme of the present invention can improve the powder combustion efficiency and the actual released heat and stability. The combustion calorific value of the aluminum-lithium alloy powder in the comparative example of the present invention is lower than that of the uncoated aluminum-lithium alloy powder, because the content of effective components is reduced after coating and after adding hydrofluoric acid, water is generated by reaction, and water reacts with lithium element, thereby reducing the content of active components.

[0057] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A method for preparing a modified aluminum-lithium alloy powder, characterized in that: include: dispersing aluminum-lithium alloy powder in an organic solvent to obtain a first alloy powder dispersion; Passing dry inert gas into the first alloy powder dispersion, and then adding hydrofluoric acid to obtain a second alloy powder dispersion after reaction; dissolving a coating agent in the organic solvent to obtain a coating agent solution, wherein the coating agent includes cellulose acetate and a wax substance; The coating agent solution is added to the second alloy powder dispersion, and stirred at a preset temperature to allow the organic solvent to volatilize and the coating agent to coat the alloy powder, followed by vacuum drying to obtain modified aluminum-lithium alloy powder.

2. The preparation method according to claim 1, characterized in that: The average particle size of the aluminum-lithium alloy powder is 1 μm to 100 μm.

3. The preparation method according to claim 2, characterized in that: When the concentration of hydrofluoric acid is 1wt%-5wt%, 0.1ml-0.5ml of hydrofluoric acid is added per gram of the aluminum-lithium alloy powder.

4. The preparation method according to claim 2, characterized in that: The ratio of the mass of the coating agent to the mass of the aluminum-lithium alloy powder is 0.05-0.

2.

5. The preparation method according to claim 1, characterized in that: After adding hydrofluoric acid, the mixture is reacted at a temperature of 30° C. to 50° C. to obtain the second alloy powder dispersion.

6. The preparation method according to claim 1, characterized in that: The wax substance is paraffin.

7. The preparation method according to claim 6, characterized in that: The ratio of the mass of cellulose acetate to the mass of paraffin in the coating agent is 0.2-0.

8.

8. The preparation method according to claim 7, characterized in that: The preset temperature is 50°C to 100°C.

9. The preparation method according to claim 1, characterized in that: The organic solvent is selected from at least one of acetone, ethanol, n-heptane, ethyl acetate and acetonitrile; And / or, the vacuum drying conditions include: the vacuum degree is not greater than 0.095 MPa, and the drying temperature is 50° C. to 80° C.

10. A modified aluminum-lithium alloy powder, characterized in that: It is prepared by the preparation method according to any one of claims 1 to 9, the modified aluminum-lithium alloy powder comprises an aluminum-lithium alloy core and a coating layer coated outside the aluminum-lithium alloy core, and the coating layer comprises cellulose acetate and wax substances.

Citation Information

Cited By

  • Low-temperature plasma fluidized bed continuous coating method and system for aluminum lithium alloy powder

    CN122480323A